Predicting Transmission of Tuberculosis Mathematical Model using Adams-Moulton Three-Step Implicit Method - Tan, Kim Yeong; Isa, Syahirbanun (Enhanced Knowledge in Sciences and Technology, 2025)
Tuberculosis is an infectious disease that primarily affect the lungs and sometimes other organ. It remains a serious public health issue in Malaysia. SIR model is applied in this study for modelling infectious disease dynamics to predict the trends of tuberculosis transmission. Adams-Moulton three-step implicit method is implemented to solve SIR models. The main purposes of this study are to examine SIR model without demography and with demography as the tuberculosis transmission mathematical model and predict the tuberculosis transmission trend in Malaysia for 2024 by changing the transmission rate of tuberculosis, β and recovery rate of tuberculosis, γ. MATLAB is employed to simplify the calculation works. The results show that SIR model with demography is a better model in predicting the trend of tuberculosis transmission. In conclusion, transmission rate, β and recovery rate, γ significantly impact tuberculosis transmission trend.